The Importance of the Quality and Sustainability Labels in the Perception of the Luxury Hotel Industry - Floričić, Tamara; Pavia, Nadia; Kacun, Tara (Journal of Tourism, Sustainability and Well-being, 2024)
The paper explores valorisation of hotel service quality elements and puts them in the context of guests’ preferences related with luxury accommodation. The focus of the paper is perception of luxury hotel offer and influence of sustainability labels and excellence awards on tourists’ preferences. The purpose of the paper is a better understanding of consumers’ attitudes when choosing luxury hotel accommodation developed and awarded within the sustainability concept. The methodology includes qualitative and quantitative analysis of the defined quality elements, perception of luxury and impact of sustainable awards and certificates on consumers’ preferences. The research was conducted using an online questionnaire in the last quarter of 2021, and it was carried out on a sample of 102 respondents, guests of upscale and luxury hotels. The research results were processed using quantitative statistical methodology, including mean values, percentages, STDEV, VAR and the Chi-square test of probability, while the open-ended question was processed using qualitative methodology, and the results are presented through the new model. Interpersonal communication followed by physical facilities and characteristics of luxury hotels are highlighted as important parameters, as is the valorisation of sustainable labels and certificates. However, by testing of the research questions and expected values, the authors have learnt that guests, consumers of luxury hotel products, predominantly do not valorise sustainable awards and certificates as key factors of perception of luxury. The findings suggest that sustainable initiatives in modern hospitality are entailed; however, the perception of luxury is not conditioned by awards and certificates.The research results, as well as the acquired knowledge, could encourage hoteliers to a more meaningful and effective promotion of certificates and awards in order to present a series of investments, activities and sustainable initiatives that have resulted in a certificate of excellence. The research bridges a scientific and professional gap in understanding of advantages of labels and awards and presents a platform for future research.